THE CONCEPT OF THE MEANING OF LIFE AND HUMAN RESPONSIBILITY IN EXISTENTIALIST PHILOSOPHY (International journal of medical sciences, 2026)
The question of the meaning of life occupies a central place in existentialist philosophy, which emerged as a response to the crises of modernity, alienation, and loss of traditional values. Existentialist thinkers argue that life has no predetermined meaning and that individuals are responsible for creating meaning through their choices and actions. This article analyzes the existentialist understanding of the meaning of life and explores the concept of human responsibility as a fundamental ethical principle. By examining the ideas of key existentialist philosophers, the study highlights the significance of freedom, choice, and responsibility in shaping human existence.